PENGEMBANGAN SISTEM OTENTIKASI PADA SEBUAH APLIKASI YANG BERBASISKAN WEB - M Arif Rahman (Universitas Dharmawangsa, 2020)
The purpose of this system made is point to the additional previous system that has been exited to protect maximally. The maximal protection is not guarantee what had been done but, it is aims do depend of firewall of a system. As well as the function itself. In design this system the researcher not only using the cryptography. That contains in PHP program is MD5. Basically the applying MD5 is not enough to secure an application based on web. Therefore the researcher’s Design a random system in purpose more guarantee data or password in a database. By adding a new good system, as a result it will easier to processing secure of data accurately and also guarantee secure of data itself. The result of this research is an application in which it is able directly apply that make by the programmer itself.